2011
DOI: 10.1371/journal.pone.0028698
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mass Spectrometry Analysis Using PAcIFIC for the Identification of Plasma Diagnostic Biomarkers for Abdominal Aortic Aneurysm

Abstract: BackgroundAbdominal aortic aneurysm (AAA) is characterized by increased aortic vessel wall diameter (>1.5 times normal) and loss of parallelism. This disease is responsible for 1–4% mortality occurring on rupture in males older than 65 years. Due to its asymptomatic nature, proteomic techniques were used to search for diagnostic biomarkers that might allow surgical intervention under nonlife threatening conditions.Methodology/Principal FindingsPooled human plasma samples of 17 AAA and 17 control patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Moreover, in Figure 3, we reported the percentage of proteins identified by each author. This analysis pointed out that Acosta-Martin et al [29] identified about 77% of plasma proteins. This high percentage of identification is probably due to the use of the dataindependent shotgun proteomic strategy PAcIFIC [29].…”
Section: Go:0006955 Immune Responsementioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, in Figure 3, we reported the percentage of proteins identified by each author. This analysis pointed out that Acosta-Martin et al [29] identified about 77% of plasma proteins. This high percentage of identification is probably due to the use of the dataindependent shotgun proteomic strategy PAcIFIC [29].…”
Section: Go:0006955 Immune Responsementioning
confidence: 94%
“…Acosta-Martin et al [29], using a data-independent shotgun proteomic strategy called Precursor Acquisition Independent From Ion Count (PAcIFIC), combined with spectral counting and isobaric tandem mass tags, identified 80 proteins as statistically differentially abundant between AAA and control patients. They used pooled human plasma samples of AAA and control patients depleted of the most abundant proteins.…”
Section: Go:0006955 Immune Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the tissue of origin for the identified plasma proteins were identified and its origin was more diverse as the protein concentration decreased (Zhang et al, 2011c). Plasma has been used as a source for biomarker studies such as colorectal cancer Murakoshi et al, 2011), cardiovascular disease (Addona et al, 2011), and abdominal aortic aneurysm (Acosta-Martin et al, 2011). Even though the blood brain barrier prevents direct blood to brain interaction, neurological disorders, such as Alzheimer's disease (AD), have had their proteomes studied using plasma (Ray et al, 2007).…”
Section: Biological Materials Selectionmentioning
confidence: 99%